Brasil: desnacionalização e dependência de commodities agrícolas e minerais - Silva, Betânia Pereira (2008)
The list of Brazilian exports products remains concentrated, since the beginning of the formation of nation, in commodities primary, intensive work and natural resources products and low content of technology, while, their imports are concentrated on products with high and medium intensity of technology. Thus, Brazil has a structural dependence profile for those exports as motor primus of national economic dynamics and a strong dependence of foreign technology. These dependencies are aggravated by the historical deficit in currents account and by the deepening of economy denationalization, which determine the need to refer profits, dividends, royalties and licenses, and to pay interest of loans to the outside, corroding, thus, a great part of currency generated by exports. The data presented in this work allow to note that in Brazil there is not a trend of reprimarization, because, actually, the dependence relation with primary products has not yet been broken.